Waldemar Espinoza Soriano and the didactics of history - Pacheco Peña , Eduardo (2021)
The study is part of an analysis of the notebooks of the young student Marino Pacheco Sandoval when he attended the chairs of Waldemar Espinoza Soriano, between 1962 and 1966 in the undergraduate of the Faculty of Education of the National University of Central Peru. This written source reveals the historian's little-known educational work during his stay in the Mantaro Valley. Espinoza Soriano influenced a host of restless students of Social Sciences, History, Philosophy and Folklore with his didactics of history.